Analisis Pengelolaan Dana Dekonsentrasi Provinsi Sumatera Selatan - Sabtrianti, Vera; Syuroh, Mat; Mahriadi, Nopriawan (@-Publik: Jurnal Administrasi Publik, 2025)
The aim of allocating deconcentration funds is to foster national harmony and synergy between deconcentration assistance programs and activities/tasks funded from the APBN and decentralization programs and activities funded from the APBD. The aim of this research is to analyze the management of deconcentration funds in South Sumatra Province. This research uses qualitative descriptive analysis techniques. Conclusion: (1). Planning consisting of dimensions of targets to be achieved, namely Deconcentration Funds and assistance tasks used to fund programs/activities that are the business of the central government, regulations used in this activity, namely Law 33 of 2004 concerning Financial Balance between the Central Government and Regional Government, Number Law Number 17 of 2017 concerning State Finance. (2). In terms of organizing, the implementing human resource indicator is 9 people, the Head of the Regional Secretariat Bureau for South Sumatra Province determines the implementing organizational structure and deconcentration funds with a division of work according to the main tasks and positions held by each personnel. (3). The South Sumatra Province Deconcentration Fund Management process and mechanism is carried out in accordance with applicable laws and regulations. (4). The supervision dimension includes external supervision and internal supervision in the Management of South Sumatra Province Deconcentration Funds, both from the Inspectorate and BPKP.